2007
DOI: 10.1152/japplphysiol.00637.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on adipose resistance artery vasoconstriction: possible implications for orthostatic blood pressure regulation

Abstract: The purpose of this investigation was to determine mean arterial pressure (MAP) and regional vascular conductance responses in young and aged Fisher-344 rats during orthostatic stress, i.e., 70 degrees head-up tilt (HUT). Both groups demonstrated directionally different changes in MAP during HUT (young, 7% increase; aged, 7% decrease). Vascular conductance during HUT in young rats decreased in most tissues but largely remained unchanged in the aged animals. Based on the higher vascular conductance of white adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…It has also been previously suggested by Romijn et al (43) that the reduction of adipose tissue blood flow is likely to be one important mechanism to explain decreased free-fatty acid release in response to high intensity exercise, which then leads to preferential utilization of glucose instead of fatty acids and contributes to the increased efficiency of ATP generation for a limited O 2 availability. Additionally, it has been recently documented that the inability to increase vascular resistance in adipose tissue during exercise or to maintain mean arterial pressure during orthostatic stress in aging is largely a result of reduced α-adrenergic responsiveness of adipose tissue arterioles (44, 45). Therefore, it is concluded that reduced blood flow in adipose tissue is an acute physiological response to diminished oxygen availability during exercise, while higher blood flow in adipose tissue is needed in response to prolonged exercise that also likely associates with higher lipolysis to supply more free-fatty acids into circulation to sustain muscular work for prolonged periods (46).…”
Section: Hypoxia and Adipose Tissue Circulation And Metabolismmentioning
confidence: 99%
“…It has also been previously suggested by Romijn et al (43) that the reduction of adipose tissue blood flow is likely to be one important mechanism to explain decreased free-fatty acid release in response to high intensity exercise, which then leads to preferential utilization of glucose instead of fatty acids and contributes to the increased efficiency of ATP generation for a limited O 2 availability. Additionally, it has been recently documented that the inability to increase vascular resistance in adipose tissue during exercise or to maintain mean arterial pressure during orthostatic stress in aging is largely a result of reduced α-adrenergic responsiveness of adipose tissue arterioles (44, 45). Therefore, it is concluded that reduced blood flow in adipose tissue is an acute physiological response to diminished oxygen availability during exercise, while higher blood flow in adipose tissue is needed in response to prolonged exercise that also likely associates with higher lipolysis to supply more free-fatty acids into circulation to sustain muscular work for prolonged periods (46).…”
Section: Hypoxia and Adipose Tissue Circulation And Metabolismmentioning
confidence: 99%
“…Therefore, elevated basal vascular tone in old animals may limit the ability of the SNS to induce further vasoconstriction. In addition, it has been shown that ␣ 1 -adrenergic receptor-mediated vasoconstriction is also diminished with age in peripheral arteries (30,45), possibly further reducing the sympathoexcitatory effect of HF feeding on peripheral vascular resistance and BP in old rats compared with young. To clarify the relative importance of central regulatory mechanisms and peripheral vascular function, further studies assessing sympathetic nerve activity parallel with changes in BP will be necessary.…”
Section: Long-term Cardiovascular Effects Of Hf Feedingmentioning
confidence: 99%
“…23 Furthermore, it has been recently reported that the inability to increase adipose tissue vascular resistance during exercise or maintain mean arterial pressure during orthostatic stress with old age is largely a result of diminished α-adrenergic responsiveness of adipose tissue arterioles. 24, 25 Hence, reduced adipose tissue blood flow is one potential acute physiological adjustment in response to short-term and/or highintensity exercise. Accordingly, our results indicate that part of the redistribution of blood flow towards exercising muscle in hypoxia 18 involves vasoconstriction of adipose tissue, while increased adipose blood flow is required in response to prolonged exercise that also associates with increased lipolysis to provide free-fatty acids for muscular work.…”
Section: Discussionmentioning
confidence: 99%